Research Funding Policies and Opportunities in EU Countries in the Context of New Development Opportunities - IACOB (PÂRGARU), Oana Camelia; CHIOTAN, Radu Alexandru; GANEA, Otilia; CIOBANU, Ghenadie (European Journal of Sustainable Development, 2023)
In the context of the development of research infrastructures, necessary for the solution of economic and social challenges in the countries of the European Union, and at the global level. The branch of research is an important part of the economic cycle, and they are valued as strategic, innovation investments that contribute to national and global competitiveness. An important problem of cricketing is the transfer of knowledge/technologies in the innovation ecosystem, the adoption of innovative ideas coming from research, by SME. It is important to be able to develop and implement new research infrastructure financing principles for EU countries. In this article, we propose to carry out a comparative analysis of research funding mechanisms in the EU countries and other experiences from the USA, Japan, China, in order to be able to identify new solutions and mechanisms for funding and making research strategies, policies and management more efficient in Romania. By correlating research - development, innovation policies with funding and investment policies in the short, medium and long term, we will succeed in building a viable and functional model of scientific research in different fields of development in Romania and for EU partner countries and other partner countries. Key words Research funding policies, research infrastructures, innovation policies, research strategies